Impact of germination alone or in combination with solid-state fermentation on the physicochemical, antioxidant, in vitro digestibility, functional and thermal properties of brown finger millet flours - Azeez, Shakirah Omotoke; Chinma, Chiemela Enyinnaya; Bassey, Stella Oyom (My University, 2021)
The impact of germination alone or in combination with solid-state fermentation on the physicochemical, antioxidant, in vitro digestibility, functional, and thermal characteristics of brown finger millet were evaluated. Germination and fermentation increased (p ≤ 0.05) the protein, crude fiber, minerals, resistant starch (7.64–9.69 g/100g), total flavonoid content, total phenolic content, antioxidant properties (ABTS, DPPH and FRAP), majority of the amino acids as well as in vitro protein digestibility (67.72–89.53%), while anti nutritional factors and digestible starch (from 45.17 to 35.58 g/100 g) content decreased significantly. Germination and fermentation significantly increased water absorption capacity and protein solubility, and slightly modified the pasting and thermal characteristics of brown finger millet flour while bulk density decreased. Among the treatments, combined germination and fermentation greatly improved the physicochemical, antioxidant, functional and processing properties of the flour with reduced anti nutrients. Such combined process could enhance the use of brown finger millet as a novel flour in food product development.
Keywords: Ukamaka Roseline Eze; Ayodamola Folake Makinde; Chiemela Enyinnaya Chinma; Finger millet; Solid-state fermentation; Germination; Antioxidant; Nutritional; ACE: Mycotoxin and Food Safety; ACEMFS; Federal University of Technology, Minna; Nigeria